ANALISIS KELEMBAGAAN PENYULUHAN PERTANIAN DI KABUPATEN KAMPAR - Widya Dwi Pertiwi Pelawi; Rosnita Rosnita; Roza Yulida (Jurnal Ilmiah Pertanian, 2016)
Institutional extension is a government agency which has the task and function of organizing counseling.The enactment of the Constitution No. 32 of 2004 explained that the extensionactivities carried out in their respective offices and constitution No 16 of 2006 explaining there are special institutionscause a wide range of extension activities in each area. The objectives of this research were, reviewing the vision and mission extension agents, analyze the role and function of the structure based on each institution, reviewing the policy rule extension, reviewing each program extension agency. The research was conducted at BPPKP in Kampar district. The number of respondents 23 people. They are heads of field extension and head of the hall extension. The data used primary data and secondary data. Primary data was taken through the interview method. Data analysis using descriptive methods.The results showed that mission and vision led to the development of natural resources and human resources, the role functions and duties of each structure has not been fully implemented properly in accordance with policy rules and extension activities have not been operating effectively and efficiently, rules defined policy has not done well in which BPPKP yet fully guided by the Constitution No. 16 of 2006 and extension activities are not polyvalent, programa prepared based on the needs of farmers. The problem are: deficiency of shortages, the Constitution No. 16 of 2006has not been implemented and extension activities are not polyvalent